2019
DOI: 10.1016/j.htct.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Sex-divided reference intervals for mean platelet volume, platelet large cell ratio and plateletcrit using the Sysmex XN-10 automated haematology analyzer in a UK population

Abstract: Background This study aimed to define the sex-divided reference intervals for platelet indices (mean platelet volume (MPV), platelet distribution width (PDW), platelet large cell ratio (P-LCR) and plateletcrit (PCT)) on the Sysmex XN-10. Methods A total of 2376 samples were assayed for full blood count on the Sysmex XN-10 haematology analyzer. After removing the outliers, reference intervals were calculated using the mean ± 2SD. The P value 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…An important aspect was the sample size analyzed in the mentioned study and, as highlighted by Ali et al, the results obtained confirmed reports in the literature 14 . However, when compared to other studies, the findings were discordant, and support the relevance of establishing reference intervals for each region and specific population as recommended by the Clinical and Laboratory Standards Institute (CLSI) 15 .…”
supporting
confidence: 80%
See 2 more Smart Citations
“…An important aspect was the sample size analyzed in the mentioned study and, as highlighted by Ali et al, the results obtained confirmed reports in the literature 14 . However, when compared to other studies, the findings were discordant, and support the relevance of establishing reference intervals for each region and specific population as recommended by the Clinical and Laboratory Standards Institute (CLSI) 15 .…”
supporting
confidence: 80%
“…Several laboratory parameters have specific reference values for men and women due to differences in anatomical structure, muscle mass or hormonal profile 13 . Specifically for the determination of platelet indices, there are contradictory reports about these differences 5, 13, 14…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These cell counters adopt or combine impedance and optical measurements of platelet dimensions 25 . The proportion of large cells is variable reflected by broad P‐LCR reference ranges between 17.6% and 47.0% in males and 17.8% and 47.8% in females 26 …”
Section: What Is a Mean A Large And A Small Platelet?mentioning
confidence: 99%
“…25 The proportion of large cells is variable reflected by broad P-LCR reference ranges between 17.6% and 47.0% in males and 17.8% and 47.8% in females. 26 Instead, no standardized parameter to quantify small platelets exists. At least for scientific reasons a definition of a "platelet small cell ratio" would be desirable.…”
Section: What Is a Me An A L Arg E And A S Mall Pl Atele T ?mentioning
confidence: 99%